When we found home ebook - Mallery, Susan (2018)
Becoming a family will take patience, humor, a little bit of wine and a whole lot of love After life knocked Delaney Holbrook sideways, she didn't get down—she got busy. She went back to school, determined to reinvent herself. She even swore off men in suits. But then one particular man in one very fine suit proves too tempting to resist—Malcolm Carlesso, CEO of a family-owned food company. Malcolm's life has been complicated by the arrival of two half sisters he's never met...and isn't sure he wants around. How can Delaney trust a man who keeps his own sisters at such a distance? Alone in the world, Callie Smith never expected to find a family. Suddenly she's living in a house the size of a small country with her stuffy and aloof new brother and streetwise sister, wondering whether this place—and these people—will ever feel like home. Just as she's beginning to get settled, a new opportunity presents itself, daring her to dream of more...until her past threatens to take it all away. Friends brought together by chance, Delaney and Callie will soon discover the closest families are bonded by choice—not by blood—in this uplifting story from the consistently unputdownable Susan Mallery. Don't miss New York Times bestselling author Susan Mallery's heartwarming summer novel, The Summer Book Club , where conversations over a glass of wine turns into something much more in this journey of motherhood, friendship and love. Get lost in more beach reads by Susan Mallery: The Summer Book Club - Coming February 2024! The Happiness Plan The Sister Effect The Boardwalk Bookshop The Summer Getaway